2023
DOI: 10.1186/s12894-023-01213-w
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and functional outcomes after bilateral sacrospinous colposuspension (BSC) for the treatment of female genital prolapse

Abstract: Background Pelvic organ prolapse is a bothersome condition affecting many women at advanced age, but also frequently observed in young women with certain risk factors. Various surgical techniques have been developed with the aim of providing effective surgical treatment for apical prolapse. The vaginal bilateral sacrospinous colposuspension surgery (BSC) with ultralight mesh and utilization of the i- stich is a relatively new minimal invasive technique with very promising outcomes. The techniqu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…As stated by Prof. Kieback who designed the BSC mesh™ [5], bilateral correction allows symmetrical suspension of the vaginal apex and the creation of neo-ligaments inserting on the sacrospinous ligament. In comparison with the unilateral Richter's sacrospinofixation where there may be a recurrence of the anterior compartment mainly related to the deviation of the vaginal axis, the BSC mesh™ keeps the vagina in a more horizontal plane closer to the original anatomic position [17]. We did not record any hematoma or hemorrhagic complications since there is no extensive dissection of the pararectal fossa with this vaginal minimally invasive technique.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…As stated by Prof. Kieback who designed the BSC mesh™ [5], bilateral correction allows symmetrical suspension of the vaginal apex and the creation of neo-ligaments inserting on the sacrospinous ligament. In comparison with the unilateral Richter's sacrospinofixation where there may be a recurrence of the anterior compartment mainly related to the deviation of the vaginal axis, the BSC mesh™ keeps the vagina in a more horizontal plane closer to the original anatomic position [17]. We did not record any hematoma or hemorrhagic complications since there is no extensive dissection of the pararectal fossa with this vaginal minimally invasive technique.…”
Section: Discussionmentioning
confidence: 83%
“…In a retrospective study of 30 patients with a 1-year follow-up, Hosni et al [17] found that the POP-Q parameters were significantly improved at twelve months after surgery compared to the baseline. The rate of anatomical success at one year was 100%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation